2014
DOI: 10.1364/oe.22.010693
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic dipole radiation tailored by substrates: numerical investigation

Abstract: 8Nanoparticles of high refractive index materials can possess strong magnetic polarizabilities and give 9 rise to artificial magnetism in the optical spectral range. While the response of individual dielectric or 10 metal spherical particles can be described analytically via multipole decomposition in the Mie series, the 11 influence of substrates, in many cases present in experimental observations, requires different approaches. 12Here, the comprehensive numerical studies of the influence of a substrate on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 39 publications
5
52
0
Order By: Relevance
“…The solutions for this problem proposed earlier , albeit finding their applications for modelling the near‐field of low‐index nanoparticles on metallic substrates , involve laborious calculations. Thus, most of the analysis of the scattering of nanoparticles on substrates tends to be either qualitative or based on finite element methods . A promising analytical model was proposed recently in the work by Miroshnichenko et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The solutions for this problem proposed earlier , albeit finding their applications for modelling the near‐field of low‐index nanoparticles on metallic substrates , involve laborious calculations. Thus, most of the analysis of the scattering of nanoparticles on substrates tends to be either qualitative or based on finite element methods . A promising analytical model was proposed recently in the work by Miroshnichenko et al.…”
Section: Introductionmentioning
confidence: 99%
“…The most convenient way to manipulate the optical response of high-index nanoparticles is by changing their size and geometry [13,17,[32][33][34][35]. Alternatively, recent studies [27,30,36] showed that the dielectric permittivity of the environment (i.e., the substrate) also has strong impact on the optical properties of dielectric nanoparticles. Namely, low-index glass substrate was reported to reduce the scattering efficiency and Q-factors of optical resonances of high-index nanoparticles [27,30].…”
Section: Introductionmentioning
confidence: 99%
“…Scattering efficiency is a dimensionless parameter measuring the total scattered power, normalized with respect to the incident intensity and the geometric cross section of the scatterer. For the individual Au and Si nanospheres, notable differences in Qsca are observed between both excitation schemes due to the presence of a substrate, which breaks the symmetry between TE\TM excitations under oblique incidence. In the case of the heterodimer, the heterogeneity breaks the mirror symmetry of the nanostructure, that is, xz is not a plane of mirror symmetry.…”
Section: Resultsmentioning
confidence: 99%
“…This fact is also related to the reduction of optical contrast between the Si NPs and surrounding medium, being even more harmful for NPs from materials with a lower refractive index (e.g., TiO 2 as shown in the ESI †). When Si NPs are located on the perovskite surface the resonant conditions are not strongly affected by the dielectric substrate, 43,44 whereas light confinement and the Mie resonances become much weaker for Si NPs inside the dielectric surrounding medium with a relatively large value of refractive index. In order to compare the absorption increase in different geometries, it is reasonable to compare the integrals over a broad spectral range (650-950 nm) by using the following formula:…”
Section: Modelingmentioning
confidence: 99%